A DFT study of solvation effects and NBO analysis on the tautomerism of 1-substituted hydantoin - Meisam Shabanian; Hassan Moghanian; Mohsen Hajibeygi; Azin Mohamadi (Arabian Journal of Chemistry, 2016)
1-Substituted hydantoins (1-SH) have been known as a benefit intermediate for producing agricultural and pharmaceuticals. The effect of solvent polarity on the tautomeric equilibria of 1-substituted hydantoin ring is studied by the density functional theory calculation (B3LYP/6–31++G(d,p)) level for predominant tautomeric forms of hydantoin derivatives (1-NO2, 1-CF3, 1-Br, 1-H, 1-CHCH2, 1-OH, 1-CH3) in the gas phase and selected solvents (benzene (non-polar solvent), tetrahydrofuran (THF) (polar aprotic solvent) and water (protic solvent)). For electron withdrawing and releasing derivatives in the gas phase and solution Hy1 forms is more stable and dominant form. In addition variation of dipole moments and charges on atoms in the solvents are studied.